Existe-t-il une nouvelle géographie socialiste au Venezuela ? Justice spatiale et justice sociale dans la révolution bolivarienne de Hugo Chavez - Jean-Marc Fournier (Cybergeo)
This article seeks to assess the geographical impact of Venezuela’s Bolivarian revolution. It compares the rhetoric of the revolution with empirical facts by studying regional imbalances and socialist programs implemented in the state of Zulia in both rural and urban areas. The concepts of spatial justice and social justice are used to try to understand how this new socialist geography can contribute to the country’s development. Despite the advances of the revolution, the oil rent-seeking capitalism heritage of the 20th century continues. If we can observe a greater territorial and social integration of the poor and excluded people, which is sometimes more symbolic than real, this has not really generated a greater spatial and social justice to them. This is true within the selected definition of the justice, at the present time and within the studied geographical areas.